Estimation of HbA1c level among diabetic patients using second derivative of photoplethysmography - Usman, Sahnius (Institute of Electrical and Electronics Engineers Inc., 2018)
Diabetes mellitus has become very important issue over the last decade. It affects several complications such as kidney failure, heart failure, stroke and blindness. The risk of developing diabetic complications is related to hyperglycemia and duration of having diabetes. Therefore, early detection can improve the chances of therapeutic interventions that may alleviate its effects. This research proposed second derivative of Photoplethysmography waveform (SDPPG) technique for monitoring the arterial condition in estimated the states of diabetic (HbA1c level greater than 10 percent). The proposed technique is simple and low cost optical techniques for detecting and tracking blood volume change. Results showed that the risk of having HbA1c level greater than 10 percent can be estimated. We conclude that the proposed technique on extracting the information from PPG signal is useful for estimating HbA1c level greater than 10 percent among diabetic patients.